2016
DOI: 10.1073/pnas.1603907113
|View full text |Cite
|
Sign up to set email alerts
|

Dimethyl fumarate treatment induces adaptive and innate immune modulation independent of Nrf2

Abstract: Dimethyl fumarate (DMF) (BG-12, Tecfidera) is a fumaric acid ester (FAE) that was advanced as a multiple sclerosis (MS) therapy largely for potential neuroprotection as it was recognized that FAEs are capable of activating the antioxidative transcription factor nuclear factor (erythroid-derived 2)-like 2 (Nrf2) pathway. However, DMF treatment in randomized controlled MS trials was associated with marked reductions in relapse rate and development of active brain MRI lesions, measures considered to reflect CNS i… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

16
213
0

Year Published

2017
2017
2022
2022

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 260 publications
(234 citation statements)
references
References 43 publications
16
213
0
Order By: Relevance
“…The clinical benefit of DMF treatment in both Nrf2 2/2 and wild-type mice was associated with a reduction of inflammatory Th1 and Th17 cells, as well as with induction of 366 anti-inflammatory M2 monocytes. At the same time, decreased expression of CD80 and CD86 costimulatory molecules was observed in wild-type, but not in Nrf2 2/2 mice, indicating that at least these effects were NRF2-dependent (Schulze-Topphoff et al, 2016).…”
Section: A Electrophilic Nuclear Factor (Erythroid-derived 2)-like 2mentioning
confidence: 88%
“…The clinical benefit of DMF treatment in both Nrf2 2/2 and wild-type mice was associated with a reduction of inflammatory Th1 and Th17 cells, as well as with induction of 366 anti-inflammatory M2 monocytes. At the same time, decreased expression of CD80 and CD86 costimulatory molecules was observed in wild-type, but not in Nrf2 2/2 mice, indicating that at least these effects were NRF2-dependent (Schulze-Topphoff et al, 2016).…”
Section: A Electrophilic Nuclear Factor (Erythroid-derived 2)-like 2mentioning
confidence: 88%
“…Importantly, whereas oral administration of DMF protects against EAE, this protection was lost in mice lacking HCA2 expression (45). Moreover, DMF was equally protective against EAE in both wild-type and Nrf2−/− mice, suggesting that the observed beneficial effects of DMF in MS are independent of Nrf2 activation (46). …”
Section: No2-fa Therapy At the Intersection Of Other Successful Pharmmentioning
confidence: 99%
“…DMF can induce apoptosis in circulating immune cells, including lymphocytes and monocytes,8, 9 and exerts anti‐inflammatory effects on both peripheral and CNS‐resident immune cells 3, 10, 11. Recent reports have demonstrated that the Nrf2‐dependent induction of AREs by DMF may be dispensable for neuroprotection, and the influence of DMF on both the innate and adaptive immune response may be the principle mechanism of action 12. Furthermore, it has been demonstrated that the anti‐inflammatory effects of fumarates may be restricted to DMF, with other fumarate metabolites having little influence on inflammation 9, 10, 13, 14.…”
Section: Introductionmentioning
confidence: 99%